Freedom jazz dance: la lotta per la libertà nel free jazz - Catalano, Raul (Scenari, 2021)
Since its origins jazz has had a close relationship with freedom: the need to experiment felt by its protagonists has produced music in continuous movement but also respectful of its tradition. With the present essay we propose two objectives: to describe a historical phase of jazz in which this search of freedom was very important assuming also political connotations, Free jazz. Secondly, we want to show the philosophical and social implications of the practice on which the activity of the Free pioneers, improvisation, was based.